Migrants’ Social Integration and Its Relevance for National Identification: An Empirical Comparison Across Three Social Spheres - Becker, Charlotte Clara (Frontiers in Sociology, 2022)
A key element of migrants’ well-being is their emotional integration, that is, the extent to which they perceive themselves as members of society and their identification with the country they are living in. To foster this sense of belonging, many integration programs aim to increase the migrants’ social integration, for example, by organizing events for migrants to meet natives in various settings. The validity of this strategy is supported by decades of international research. It remains unclear, however, which aspects of social integration are most relevant for national identification. Multiple theories concerned with contact and group identification support the assumption that contact to natives should foster a sense of belonging and national identification. However, for a contact situation to bear this potential, a certain set of criteria, including aspects like direct personal contact, a similar social status, and the presence of egalitarian norms, needs to be fulfilled. It is expected that these characteristics are more likely to be fulfilled within family and friendship settings than in contact situations within the employment context. Hence, I expect contact to natives within the network of friends and family to be more greatly associated with migrants’ national identification. I analyzed data from a 2013 cooperation between the Institute for Employment Research (IAB) and the German Socio-Economic Panel (SOEP), that is, the IAB-SOEP Migration Sample, as well as the 2014 wave of the SOEP. The subsample used included 2,780 first- and second-generation migrants living in Germany. The results indicate that not all kinds of contact are equally linked to national identification. In contrast to expectations, in neither the cross-sectional models nor the lagged models was living together with native family members significantly linked to national identification. Similarly, the association between having predominantly native co-workers and national identification was insignificant when controlling for migrant-specific characteristics. Only the relation with having predominantly native friends was significant and positive across all models. This as well as a comparison of the associations lead to the conclusion that when it comes to migrants’ national identification native friends might be the most relevant form of contact to natives.